Probiotic Supplements do not Increase the Effectiveness of Antibiotics in the Treatment of Bacterial Vaginosis: Suplemen Probiotik tidak Meningkatkan Efektivitas Antibiotik dalam Terapi Bakterial Vaginosis - Ratnah Hamid; Eddy Tiro; Josephine Tumedia (Indonesian Journal of Obstetrics and Gynecology, 2013)
Objective : This study aims to assess the effect of the addition of probiotic supplement to the standard therapy on the recovery of Bacterial vaginosis infection. Methods: The research was conducted by taking samples from Obstetrics and Gynecology Department in several teaching hospitals of Faculty of Medicine, Hasanuddin University. This study was an experimental study. Consecutive sampling was conducted on 50 samples, which were then divided into two groups. Group 1 received Metronidazol therapy 2 times a day for 7 days, while group 2 received Metronidazol therapy 2 times a day supplemented with oral Probiotic of once a day for 7 days. The data were analysed by using the chi-square test. Results: There is no significant difference in the recovery of bacterial vaginosis infection between the group that received the probiotic supplementation and the group that did not. Conclusion: The addition of probiotic supplement to the standard therapy of BV infection does not show any signifcant effect. [Indones J Obstet Gynecol 2013; 1-4: 194-8] Keyword: bacterial vaginosis, probiotic supplement, recovery, standard therapy